Ireland's gramophones : material culture, memory, and trauma in Irish modernism - Cammack, Zan (Clemson, SC : Clemson University Press, 2021)
"Ireland's Gramophones examines the perpetual presence of the gramophone in literature of Irish modernism: the same period in which gramophonic technology grew to cultural prominence. The book argues that the gramophone, as object and instrument, embodies accounts of a culture frequently traumatized through violence and disruption"--
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on October 08, 2021).
JSTOR
Keywords: Phonograph in literature; English literature -- Irish authors -- History and criticism; Modernism (Literature) -- Ireland; Collective memory in literature; Littérature anglaise -- Auteurs irlandais -- Histoire et critique; Modernisme (Littérature) -- Irlande; Mémoire collective dans la littérature.; Social & cultural history; History -- Europe -- Ireland; Collective memory in literature; English literature -- Irish authors; Modernism (Literature); Phonograph in literature; Ireland; Irish Modernism; gramophones; Thing theory; cultural studies; trauma; Criticism, interpretation, etc; Literary criticism; Literary criticism; Critiques littéraires.